2007
DOI: 10.1111/j.1477-9730.2007.00446.x
|View full text |Cite
|
Sign up to set email alerts
|

Airborne digital imaging technology: a new overview

Abstract: This paper presents an overview of current developments in the airborne digital imaging technologies—including both digital frame cameras and pushbroom line scanners—and analyses them in the context of their applications to digital photogrammetry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 2 publications
0
38
0
Order By: Relevance
“…The radiometrically stable instrument belongs to a new generation of airborne sensors, aimed at replacing older analogue airborne cameras used for surveying and topographic mapping (Petrie and Walker, 2007). In Switzerland, the Federal Office of Topography (swisstopo) and Leica Geosystems operate ADS40 instruments.…”
mentioning
confidence: 99%
“…The radiometrically stable instrument belongs to a new generation of airborne sensors, aimed at replacing older analogue airborne cameras used for surveying and topographic mapping (Petrie and Walker, 2007). In Switzerland, the Federal Office of Topography (swisstopo) and Leica Geosystems operate ADS40 instruments.…”
mentioning
confidence: 99%
“…Jaakkola et al [10] proposed automatic methods of road surface modeling using laser-based mobile mapping. Petrie [2,11] organized various LMMS equipment and relevant services, as well as equipment suppliers, to build a 3D geographical information database. Rau et al [12] showed a single-step system calibration method for direct sensor orientation of an LMMS.…”
Section: Introductionmentioning
confidence: 99%
“…The Swiss Federal Office of Topography changed to working with digital data from airborne ADS40 sensors in 2008 (Kellenberger and Nagy 2008). The digital device is supposed to be spectrally and radiometrically superior to the analogue RC30 cameras (Petrie and Walker 2007). A satellite SPOT5 mosaic has also recently become available for the whole area of Switzerland.…”
Section: Introductionmentioning
confidence: 99%